IMPLEMENTASI KEBIJAKAN WALI KOTA PONTIANAK NOMOR 30 TAHUN 2024 TENTANG PELAKSANAAN HARI RAYA IDULADHA TANPA SAMPAH PLASTIK - Fuzy Firda Zhan; Etika Khairina; Hani Alfiyani (PUAN INDONESIA, 2026)
The environmental threat of plastic waste has prompted the Pontianak City Government to issue a plastic-free Eid al-Adha policy through Pontianak Mayor's Circular Letter Number 30 of 2024 concerning the Implementation of Eid al-Adha Without Plastic Waste, which aligns with the Circular Letter of the Minister of Environment and Forestry of the Republic of Indonesia Number: SE.6/MENLHK/PSLB3/PLB.0/6/2024. The purpose of this study is to analyze the implementation of the plastic-free Eid al-Adha policy in Pontianak City. The research method used is descriptive with a qualitative approach. Data were obtained from observation, documentation studies, and literature reviews. The results of this study found that the Pontianak City Government, through the Pontianak City Environmental Agency, implemented the policy through three stages: (1) outreach and education; (2) provision of supporting facilities; and (3) collaboration with various communities. Implementation of this regulation still faces challenges, including providing subsidies from the government or corporate CSR programs, establishing partnerships with local artisan MSMEs, and establishing a bank or loan program. Furthermore, strengthening regulations, monitoring implementation, and enforcing sanctions are also necessary for the plastic-free Eid al-Adha policy.